c-Jun protein effect on regulating CD4+ and CD8+ T cell proliferation in H1N1 influenza A virus infected mice - ZHANG Shouping; SHEN Wentao; WANG Lirong; ZHANG Baizhong (浙江大学学报. 农业与生命科学版)
A H1N1 influenza A virus infected mice model was built to evaluate the regulation mechanism of c-Jun protein in T lymphocytes. To determine the DNAzyme Dz13 efficiency in virus-infected animals, a Western-blotting assay was employed to detected total c-Jun (t-c-Jun) and phosphorylation c-Jun (p-c-Jun) levels by specific antibody. It was demonstrated that the drug-treated mice markedly suppressed the expression of t-c-Jun and p-c-Jun. Through flow cytometry and quantitative real-time polymerase chain reaction (qRT-PCR), we could find an obvious CD4+ (helper T lymphocytes) and CD8+ T (cytotoxic T lymphocyte) cell proliferation and relative cytokine (IFN-γ, IL-6 and IL-10) expression on day 3 and 6 in the virus-infected mice. The Dz13-treated mice with a c-Jun suppression displayed a down-regulation of CD4+ and CD8+ T cells in peripheral blood. At the same time, Dz13-treated group demonstrated a significant reduction of inflammatory cytokine (IFN-γ, IL-6 and IL-10) expression. In conclusion, c-Jun protein regulates CD4+ and CD8+ T cell proliferation and inflammatory cytokine expression in H1N1 influenza A virus infected mice.